How do you factor x2 + 5x - 6?

We need to factorise the given equation

Given equation

x2 + 5x – 6

Let us try factorizing this polynomial using splitting the middle term method.

Factoring polynomials by splitting the middle term:

We need to find two numbers ‘a’ and ‘b’ such that a + b =5 and ab = 6.

On solving this we obtain, a = 3 and b = 2

Thus, the above expression can be written as:

x2 + 5x – 6

= x2 +6x -x – 6

= x(x + 6) -1(x + 6)

= (x + 6)(x -1)

Thus, x+6 and x-1 are the factors of the polynomial x2 + 5x – 6.

Leave a Comment

Your email address will not be published. Required fields are marked *

BOOK

Free Class